Software-aided measurement of geometrical fidelity for 3D printed objects. Issue 4 (7th June 2017) - Baumann, Felix W.; Wellekötter, Jochen; Roller, Dieter; Bonten, Christian
ABSTRACT: This research evaluates the geometric fidelity of 3D printed objects by utilizing digital image analysis techniques on consumer grade 3D printers. ISO 527-2 Type B specimen are modeled using Houdini Software, then positioned on the virtual print-bed and sliced in 0.3 mm thickness layers utilizing MiracleGrue slicer. The specimens are printed on a Makerbot Replicator2X 3D printer with an X-Y resolution of 0.011 mm. The test set is divided into three where the first object set (Test set A) is printed with their longest side parallel to the X axis, the second object set (Test set B) with their longest side oriented at an angle to the X axis and the third object set (Test set C) as a control with a different material type and structure. The test includes objects with parallel patterns of 0, 5, 10, 30, 45, 60 and 90 degree resulting in toolpaths along the parallel lines. For the second test set the orientation angle is chosen to match the parallel pattern degree. The objects are analyzed with a software developed for this purpose. For image data acquisition a scanner is employed. This work shows that high quality geometric information can be deduced from scanned image data for the analysis of the geometric fidelity of flat or thin 3D printed objects. This work also displays enhancements possible to the proposed algorithm and software. With this research we present a low cost and unobtrusive method to perform geometrical analysis for flat printed additively manufactured objects. By providing a software component that is able to extract geometrical information from existing models (as STL or STEP files) and matches them digitally acquired images from printed objects we are able to ascertain the geometric fidelity of 3D printed objects under the influence of varying filling patterns and object orientation. GRAPHICAL ABSTRACT: